2017
DOI: 10.1158/1078-0432.ccr-16-0772
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Study of the Anti-CD22 Antibody–Drug Conjugate Pinatuzumab Vedotin with/without Rituximab in Patients with Relapsed/Refractory B-cell Non-Hodgkin Lymphoma

Abstract: Purpose Pinatuzumab vedotin is an antibody–drug conjugate with the potent antimicrotubule agent monomethyl auristatin E (MMAE) conjugated to an anti-CD22 antibody via a protease-cleavable linker. This phase I study determined its recommended phase II dose (RP2D) and evaluated its safety, tolerability, and antitumor activity alone and with rituximab in relapsed/refractory (r/r) non-Hodgkin lymphoma (NHL) and chronic lymphocytic leukemia (CLL). Experimental Design Patients received escalating doses of pinatuzu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 31 publications
4
43
0
Order By: Relevance
“…The efficacy of blinatumomab in this study is comparable to that of the novel compounds with the best published results in r/r DLBCL, including the conjugate antibodies pinatuzumab vedotin (ORR, 39%) 20 and 90 Y-ibrutumomab tiuxetan (ORR, 53%), 21 lenalidomide (ORR, 35%), 22 and the anti-PD1 antibody nivolumab (ORR, 36%). 23 Lower response rates have been reported for other new drugs as monotherapy in r/r DLBCL, including inotuzumab ozogamicin (ORR, 15%), 24 the Bruton tyrosine kinase inhibitor ibrutinib (ORR, 22%), 25 and the phosphoinositol-3 kinase inhibitor buparlisib (ORR, 12%).…”
Section: Discussionsupporting
confidence: 72%
“…The efficacy of blinatumomab in this study is comparable to that of the novel compounds with the best published results in r/r DLBCL, including the conjugate antibodies pinatuzumab vedotin (ORR, 39%) 20 and 90 Y-ibrutumomab tiuxetan (ORR, 53%), 21 lenalidomide (ORR, 35%), 22 and the anti-PD1 antibody nivolumab (ORR, 36%). 23 Lower response rates have been reported for other new drugs as monotherapy in r/r DLBCL, including inotuzumab ozogamicin (ORR, 15%), 24 the Bruton tyrosine kinase inhibitor ibrutinib (ORR, 22%), 25 and the phosphoinositol-3 kinase inhibitor buparlisib (ORR, 12%).…”
Section: Discussionsupporting
confidence: 72%
“…Various anti‐CD22 antibodies have been mapped to the first four Ig domains, including To15 , IS7 , BL‐3C4 , HD6 , RFB4 , LL2 [humanized as epratuzumab ], G5/44 (a humanized CD22 antibody linked by an acid‐labile linker to the cytotoxic drug calicheamicin to form inotuzumab ozogamicin or CMC‐554) and 10F4 . The latter four have been tested clinically either as naked antibodies or linked to radioisotopes, cytotoxic drugs or toxins for the treatment of B‐cell lymphomas or leukemias . The RFB4 antibody, targeting Ig domain 3 , has no antitumoral activity by itself, but regresses various CD22‐expressing B‐cell xenografts when conjugated to the antimitotic drugs DM1 (a maytansinoid) or MMAE (auristatin E, a synthetic dolastatin‐10 derivative) .…”
mentioning
confidence: 99%
“…Pinatuzumab vedotin also targets CD22, but the antibody moiety is conjugated, via stable linkage, to MMAE [31] . Recent human trials with this ADC have shown that rituximab can be combined with pinatuzumab vedotin; preliminary efficacy signals suggest an improvement of the combination compared to the ADC alone [32] , [33] . It is unclear whether the mechanisms involved in the CD20 and CD22 combinations are similar or distinct from those described here for our CD37-targeting ADC.…”
Section: Discussionmentioning
confidence: 99%